(untitled) - Hall, Katherine L. (West Nyack, N.Y., 1997)
A flexible, high-interest program for grades 1-3 that can be used with all regular and special students. Each volume provides more than 45 factual stories with related teaching materials.
Keywords: Reading (Primary),Reading comprehension,Đọc (Tiểu học),Đọc hiểu; Problems, exercises, etc.,Problems, exercises, etc